Assessment of Social Vulnerability and Post-Earthquake Affected Areas in Sumedang Regency - Ihsan, Haikal; Rohmat, Dede; Arrasyid, Riko; Suhendro; Albanah, Rosa; Lestari, Sri (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2025)
This research aims to map social vulnerabilities and affected areas after the earthquake in Sumedang Regency. Social vulnerability was mapped using scoring adapted from the Regulation of the Chairman of the National Disaster Management Agency number 2 of 2012 which researchers modified according to existing data in 2024. Social vulnerability data is population density, sex ratio, vulnerable age group ratio, population ratio poor and disabled population ratio. The affected areas were mapped using field surveys and visualized using Geographic Information System (GIS) software. However, previous studies have not yet integrated dynamic post-disaster social changes or validated the vulnerability classifications with real-time community resilience indicators. Based on research, it was found that Sumedang Regency has 11 sub-districts including high classification, 8 sub-districts with medium classification and 7 sub-districts with low classification. The high classification of social vulnerability is in the central urban area of Sumedang Regency and the southern area bordering Bandung Regency. The survey results show that an area with a radius of 2 km is a very vulnerable area, a radius of 4 km is vulnerable and 6 km is medium. Based on the results of the analysis, it was found that areas with high social vulnerability and those affected by earthquakes were very vulnerable, namely North Sumedang District, Cisarua District, Cimalaka District and Ganeas District.